Association of 6-year waist circumference gain and incident hypertension. Issue 17 (7th April 2017) - Zhao, Yang; Zhang, Ming; Luo, Xinping; Wang, Chongjian; Li, Linlin; Zhang, Lu; Wang, Bingyuan; Ren, Yongcheng; Zhou, Junmei; Han, Chengyi; Pang, Chao; Yin, Lei; et al.
Abstract : Objective: The risk of incident hypertension with gain in waist circumference (WC) has not been fully addressed among Chinese adults. Methods: A total of 10 265 non-hypertensive participants ≥18 years old who underwent health examinations in rural China were recruited in 2007–2008 and followed up in 2013–2014. Participants were classified by gender according to categories of per cent WC gain at follow-up: ≤−2.5%, −2.5% to 2.5%, 2.5% to 5% and >5%. Relative risk (RR) and 95% CI values for effect of WC gain on the incident hypertension were calculated by using modified Poisson regression models. Results: During 6 years of follow-up, we identified 2027 hypertension cases (1213 women). From baseline to follow-up, the prevalence of abdominal obesity increased from 21.1% to 29.6% for men and 49.8% to 61.9% for women. As compared with participants who were not abdominally obese at both baseline and follow-up, both genders who were abdominally obese at follow-up showed greater risk of hypertension regardless of abdominal obesity status at baseline. Compared with the reference group of −2.5% to 2.5% change in WC, with >5% WC gain, risk of incident hypertension was increased for men (RR=1.34, 95% CI 1.15 to 1.57) and women (RR=1.28, 95% CI 1.10 to 1.50). The hypertension risk decreased for men with WC loss ≥2.5% (RR=0.81, 95% CI 0.67 to 0.98). Conclusions: Abdominal obesity is seriously prevalent in China. The risk of hypertension increased significantly with increasing WC for both genders in a rural Chinese population.